Sequencing the Potato genome: Outline and first results to come from the Elucidation of the sequence of the world's third most important food crop - Visser R.G.F. (2009)
The PGSC-Peruvian team was funded by grants from the Peruvian Fund for Innovation in Science and Technology (FINCYT), the Peruvian Ministry of Agriculture (MINAG) and the Peruvian Council of Science and Technology (Concytec). Additional support was received from Universidad Peruana Cayetano Heredia, Universidad Nacional San Cristobal de Huamanga and the Peruvian Ministry of foreign affairs. The PGSC-Chilean initiative has been supported by National Commission of Scientific and Technologic Research (CONICYT) and the Foundation for the Innovation in Agriculture (FIA).